2010
DOI: 10.1111/j.1365-2052.2010.02049.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variation in the melanocortin‐4 receptor gene (mc4r) in golden retriever dogs

Abstract: Source/description: The melanocortin-4 receptor plays a central role in the regulation of energy balance. Activation of the receptor leads to decreased energy intake and increased energy expenditure. 1 Genetic variation at the melanocortin-4 receptor locus (mc4r) is associated with body measures in several species. [2][3][4] The purebred dog population is a collection of genetic isolates with highly diverging morphology. 5 Dog breeds also appear to differ in their tendency to gain weight. It would be interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…It indicated that silent mutation of MC4R genes in female dogs could affect the modulation of canine body weight, and the estrogen could be an important effective factor of MC4R function to regulate body weight of Beagle dogs. Recently, some SNPs of canine MC4R gene, such as G637T, T777C and C+33G, were found from 19 different dog breeds [16, 18]. For the SNPs G637T and T777C, no association of the variant with canine body weight, length, height, or body index score was found in 187 Golden Retrievers [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that silent mutation of MC4R genes in female dogs could affect the modulation of canine body weight, and the estrogen could be an important effective factor of MC4R function to regulate body weight of Beagle dogs. Recently, some SNPs of canine MC4R gene, such as G637T, T777C and C+33G, were found from 19 different dog breeds [16, 18]. For the SNPs G637T and T777C, no association of the variant with canine body weight, length, height, or body index score was found in 187 Golden Retrievers [18].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some SNPs of canine MC4R gene, such as G637T, T777C and C+33G, were found from 19 different dog breeds [16, 18]. For the SNPs G637T and T777C, no association of the variant with canine body weight, length, height, or body index score was found in 187 Golden Retrievers [18]. However, the associations between polymorphisms of MC4R with obesity factors [10, 15], and birth weight [17] have been verified in other animals.…”
Section: Resultsmentioning
confidence: 99%
“…The MC4R gene of the dog and red fox appeared to be less polymorphic and in both species 4 SNPs were found, including 1 missense substitution in the dog (c.637G 1 T, 213Val 1 Phe) [Skorczyk et al, 2007]. This missense SNP was analyzed in terms of morphological traits of Golden Retrievers, but no association was found [van den Berg et al, 2010]. Our study showed a comparative chromosome localization of 2 important candidate genes (FTO and INSIG2) for fat accumulation and their polymorphism for the first time.…”
Section: Discussionmentioning
confidence: 96%
“…It was suggested that the variant might be functioning normally because both valine and phenylalanine are hydrophobic [17]. This variant was identified in another more recent study [18]. In preliminary analysis of 187 Golden Retrievers, no association between the polymorphisms and morphological measures were found.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors suggested that the variant will likely affect receptor function, because this missense variant changed an amino acid residue that is highly conserved and under strong purifying selection. Furthermore, PolyPen program predicted that this polymorphism is likely damaging, although the authors conceded that this prediction needed to be experimentally verified by in vitro assays [18]. …”
Section: Introductionmentioning
confidence: 99%